PENDIDIKAN KESEHATAN BERBAHASA DAERAH TERHADAP KEPATUHAN LANSIA MELAKUKAN PENCEGAHAN PENINGKATAN TEKANAN DARAH - Lestari Lorna Lolo; Dewiyanti Dewiyanti (Jurnal Endurance, 2021)
High blood pressure or hypertension is when blood pressure, the force of blood pushing against the walls of blood vessels, is consistently too high. Hypertension attacks the elderly. Elderly is someone who is 60 years and over. The use of regional languages as a method of providing health information is rarely and never even done by health workers. This study aims to analyze the impact of local language health education on elderly compliance in preventing increased blood pressure. The design used in this study is a pre experimental design method with one group pre and posttest design method. The population was 30 elderly with stage 2 hypertension who used Tae' language. Samples were taken using total sampling method. The research was processed with the wilcoxon signed ranks test, the p value was 0.000, which was smaller than the α = 0.05. It is concluded that there is an effect of local language health education (tae ') on the level of compliance in taking preventive measures to increase blood pressure in the elderly with hypertension. Providing health education using local languages is expected to be able to change the compliance of the elderly in preventing hypertension.